KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MEMECAHKAN MASALAH GARIS DAN SUDUT DI KELAS VII SMP NEGERI 9 PALU - Darius, Cumarlin; Hadjar, Ibnu; Murdiana, I Nyoman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
The purpose of this research was to obtain a description of the mathematical representation of class VIIJ students of SMP Negeri 9 Palu in solving line and angle problems. This type of research is descriptive-qualitative. The research subjects consisted of 3 students, namely 1 student representing low ability, 1 student representing moderate ability, and 1 student representing high ability, based on the grades of even semester report cards for the 2021/2022 academic year. Collecting data using tests and interviews. In analyzing data, researchers used data reduction, data display, and conclusion drawing/verification. The results showed that subjects with low abilities had mathematical representation abilities in solving line and angle problems in problem number 1 but in solving problem number 2 they were still not good. This means that the subject meets the indicators of mathematical representation abilities which include image representation, verbal representation, and symbolic representation which are still not good. Subjects with moderate abilities have mathematical representation abilities in solving line and angle problems in question number 1 but in solving problem number 2 they do not show image representations. This means that the subject meets the indicators of mathematical representation which includes image representation, verbal representation, and symbolic representation quite well. Subjects with high ability have mathematical representation abilities in solving line and angle problems in questions number 1 and 2. This means that the subject fulfills all indicators of mathematical representation ability which include image representation, verbal representation, and symbolic representation well.